CROSS-CULTURAL ASPECTS OF LEGAL COMMUNICATION IN INTERNATIONAL LAW (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Effective legal communication in international law requires navigating diverse cultural and linguistic frameworks to ensure clarity, mutual understanding, and diplomatic engagement. This study explores cross-cultural aspects of legal communication, focusing on juridical culture, stylistic norms across legal systems, the role of neutral and diplomatic language, etiquette in international correspondence, and legal errors stemming from intercultural misunderstandings. Through qualitative analysis of legal texts, case studies, and expert interviews, the research identifies key challenges and proposes strategies for enhancing cross-cultural competence in legal practice.